Kilt trip - Kiley, Alexandra (Canary Street Press, 2024)
"Ready or Scot... Globetrotter Addie Macrae always follows her wanderlust. As a travel consultant, she jet sets around the world - anywhere but Scotland. But when she's sent on assignment to help a struggling family-run tour company in the Highlands - and save her own job - Addie packs away her emotional baggage and turns on the professional charm. Rugged as the land he loves, Logan Sutherland's greatest joy is sharing the beauty of Scotland's hidden gems...even if it means a wee bit of red ink on the company's bottom line. The last thing Logan wants is some American "expert" pushing tourist traps and perpetuating myths about the Loch Ness Monster -especially when Addie never leaves her desk to experience the country for herself. As they wage an office war, Logan discovers Addie's secret connection to Scotland: a handful of faded Polaroids of her late mother. Hoping for a truce, he creates a private tour to the places in the pictures to help Addie find closure and appreciate the enchantment in less-traveled destinations, never expecting the off-limits attraction sparking between them. But Addie's contract is almost up, and magic won't pay the bills. They can't afford distractions, but how can Addie do her job if she hasn't explored all Scotland - and Logan - have to offer?" -- Back cover